Citizenship and education trajectories among children of immigrants: A transition-oriented sequence analysis. (December 2021) - Labussière, Marie; Levels, Mark; Vink, Maarten
Highlights: Legal status of children of immigrants is often neglected in European countries. The effect of naturalisation needs to be approached from a life course perspective. Transition-oriented OM better captures mobility patterns in educational careers. Citizenship is associated with students' ability to navigate complex school systems. Abstract: During recent decades, the educational outcomes of the children of immigrants have been extensively studied, with a growing emphasis on the heterogeneity of the so-called second generation. Yet, the impact of host country citizenship on children's educational outcomes has only received limited attention so far, although children of immigrants do not get automatic birthright citizenship in most European countries. Focusing on the Netherlands, this paper compares educational trajectories among citizen and non-citizen children of immigrants. Register data and sequence analysis are used to map and cluster the trajectories of a full cohort of second-generation students from the start of secondary school. We apply a variant of optimal matching focusing on sequences of transitions, which enables us to uncover different patterns of (im)mobility within a stratified school system better than the standard approach. Multinomial logistic regressions show that students who acquire Dutch citizenship are significantly more likely to follow upward trajectories, taking advantage of the system's flexibility and "back doors". Conversely, not having Dutch citizenship is associated with a higher risk of dropout and school interruptions. These findings are in line with our theoretical expectation that, during the naturalisation process, parents acquire or further develop important resources for navigating a complex educational system such as the Dutch one.